qPCR analysis of Ty-2 and Ty-3 gene pyramided lines of tomato for resistance to tomato leaf curl New Delhi virus (ToLCNDV) - LATA, SUMAN; HUSSAIN, ZAKIR; MANGAL, MANISHA; YADAV, R K; T, VINUTHA; JAT, GOGRAJ SINGH; GOSAVI, GOKUL; KUMAR, PAWAN; PERVEEN, SHELLY; TOMAR, B S (The Indian Journal of Agricultural Sciences, 2019)
The present study was carried out at the ICAR-IARI, New-Delhi, India during 2017-18 to analyze the tomato genotypes having Ty-2 and Ty-3 genes incorporated through molecular breeding for resistance against the tomato leaf curl New Delhi virus (ToLCNDV).ToLCNDV is most predominant virus and causes huge economic loss in tomato, chilli, many cucurbits and cotton. Presently six genes Ty-1, Ty-2, Ty-3, Ty-4, ty-5 and Ty-6 are being utilized to address the tomato leaf curl disease (ToLCD). The tomato genotypes under study were grown in the field, along with susceptible and resistant checks. Genotyping was done to know the status of Ty-2 and Ty-3 genes in all the tomato samples.The tomato lines showing phenotypic resistance against ToLCNDV in the field were grown under controlled conditions in phytotron and agroinoculated with ToLCNDV genome. ToLCNDV agroinoculated tomato lines were checked for ToLCNDV specific AC4 transcript by qPCR assay.ToLCNDV specific AC4 transcript level was 4 log fold high in the susceptible check (Pusa Ruby) as compared to donor line (EC814916). However, AC4 transcript level was 2.1-2.8 log fold lower in the tomato line 218 (P. Ruby Ã—EC814916) as compared to susceptible var. Pusa Ruby. The study shows the importance of Ty-3 gene for imparting resistance against ToLCD disease in tomato.